Characterisation of Rhizome Extract (Curcuma xanthorrhiza Roxb) Ointment as an Anti-Acne Remedy - Ferdianto, Sandy Prayoga; Syafaah, Lailatus; Rohmawati, Lydia (Journal of Dedication in Community, 2023)
Skin is one of the five senses of humans that functions as a thermostat in maintaining body temperature, protecting the body from attack by microorganisms, ultraviolet rays, and regulating blood pressure. However, insufficient protection factors make the skin easily infected by bacteria that can cause skin diseases. One such disease is acne. Acne occurs when anaerobic bacteria such as Staphyloccocus aureus multiply rapidly in the deep skin layers. This study was conducted to overcome acne on the skin by using an ointment preparation made from temulawak rhizome. This research uses qualitative and quantitative methods with data collection techniques through organoleptic testing, homogeneity, pH, spreadability, adhesion, and irritation. The subjects in this study were physics students at Surabaya State University with a total of 5 students. The results showed that the organoleptic test on the preparation of temulawak rhizome extract ointment was semi-solid, brownish yellow in colour, and the distinctive smell of temulawak rhizome extract. The Ph test showed a value of 5 equal to the normal pH of the skin and no irritation on the volunteer's skin. The ointment formulation had no effect on its homogeneity and had excellent adhesion